Profiles of learning : the Basic Skills testing Program in New South Wales : 1989 - ... [et al.]; Masters, Geofferey N.; Lokan, Janice; Doig, Brian; . (Hawthorn, Vic : Australian Council for Educational Research, 1990)
Aspects of basic skills. How well are students performing? Reporting BSTP results. Procedures.
Keywords: Education; Basic Skills testing; Basic Skills Testing Program (N.S.W.)